Hydrogen impurity in SrTiO3: Structure, electronic properties and migration - Barreto, R. (2006)
The present paper reports a computational investigation of the geometry and electronic structure as well as the migration of a hydrogen impurity in the cubic SrTiO3 crystal. The study is done using an approach based on the Hartree-Fock theory and developed for periodic systems. It is found that the H impurity forms the so-called OH group at the equilibrium. Analysis of electron density within the defective region implies the enhancement in covalent chemical bonding. A possible defect migration has been also investigated. © 2007 The Royal Swedish Academy of Sciences.